THE ACTION OF UNSATURATED CYANOLACTON ON Η2Ο2+ΗΟΟ− REACTION RATE IN ABSENCE AND PRESENCE OF MICELLES (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
Using gasometric method at 303 K the action of 2-cyano-3,4,4-trimethyl-2-butene-4-olid unsaturated lacton on the Η2Ο2 + ΗΟΟ- reaction rate has been studied . Taking into consideration the fact that the mentioned lacton is oilsoluble its water-ethanol solutions, as well micellar systems obtained making use two kinds of surfactants: C12H25SO−4Na+ and C12H25 N+(CH)3Cl−. It has been established that in lacton absence: − EtOH decreases the reaction rate (R), but in presence of lacton there is some increase in R value. This phenomenon is discussed in detail.− In micellar systems the lacton action is similar. There is one difference. After some increase in micelles concentration the reaction rate in lacton presence becomes lower than the R value, determined in lacton absence. This regularity is also discussed in detail, as well as the RNO• action.
Keywords: 2-cyano-3,4,4-trimethyl-2-butene-4-olid; lacton; micellar systems; reaction rate